An investigation on using serious gaming to study human decision-making in engineering contexts. (25th September 2017) - Vermillion, Sean D.; Malak, Richard J.; Smallman, Rachel; Becker, Brittney; Sferra, Michale; Fields, Sherecce
Abstract : Serious gaming is the use of games for purposes beyond entertainment. In this paper, we investigate the use of serious gaming as a tool for research into decision-making in engineering systems design. Serious gaming provides a fully controllable environment in which to study the decision-making behavior of engineers in simulated design scenarios. However, given the nature of games and their inherent association with entertainment, it is possible that gaming environments themselves induce unexpected, or unrepresentative behavior. We present two experiments in which we investigate serious gaming as a research tool. Both experiments deal with design decisions in the presence of sunk costs and compare two approaches for communicating the decision-making scenario: (1) an interactive game and (2) a written narrative. The written narrative approach for communicating decision-making scenarios is a widely used and accepted technique for decision-making research. We find that behavior observed in the game variants did not significantly differ from behavior observed in their written narrative equivalents. This result builds confidence for the use of game-based research approaches. However, the results in this paper suggest that response distributions collected from a game have more noise than those from an equivalent written narrative.